(untitled) (Journal of Tropical Resources and Sustainable Science (JTRSS), 2023)
Beef cattle farming has become a vital sub-sector in the agriculture industry in supplying protein for the populations. The self-sufficiency ratio (SSR) of beef is not encouraging, and the import value is kept increasing for many years. Meanwhile, innovation adoption in beef cattle farming is believed to improve beef production if used correctly. However, inefficient financial management has led to improper farming practices. This study aims to identify the farm financial difference in adopting such innovations. This study involves 233 beef cattle farmers from Johor, Selangor, Kedah and Kelantan using stratified and simple random sampling. It is found that integration and silage show more significant profit changes with more than 60%, while artificial insemination and vaccination show 33% and 42% profit changes, respectively. Hence, regular meetings conducted by the extension agents are essential to ensure that adopting innovation is successful besides good cooperation among all stakeholders, including the farmers, government agencies, farmers’ associations and private sectors.